2D‐Coordination Polymers Constituted from Indium Halides and Dipyridyl N‐Donor Ligands. Issue 11 (2nd May 2021) - Schäfer, Thomas C.; Becker, Jonathan; Sedykh, Alexander E.; Müller‐Buschbaum, Klaus
Abstract: Four indium‐based, 2D coordination polymers (CP) were synthesized utilizing InCl3 and InI3 and the bidentate ligands 4, 4'‐bipyridine (bipy), 1, 2‐di(4‐pyridyl)ethylene (bpe) and 1, 2‐di(4‐pyridyl)ethane (bpa). The isoreticular networks ∞ 2 [In2 Cl6 (bipy)] (1 ) and ∞ 2 [In2 Cl6 (bpe)] (2 ) are constituted by chloride‐ and ligand‐bridged octahedra with a honeycomb like (6, 3)‐net topology (hcb topology). In contrast, ∞ 2 [(In4 Cl12 )(bpa)3 ] (3 ) consists of In4 Cl12 N6 units, with each indium atom being coordinated by chloride anions and bpa ligands in an octahedral fashion. Bpa ligands connect indium atoms in two dimensions, forming a semi‐regular uninodal 3‐c net with the point symbol (4, 8 2 ), as present in the fes topology. In ∞ 2 [(InI3 )2 (bpa)3 ] (4 ), indium is coordinated by three iodide and three bpa ligands in a meridional fashion. In contrast to ∞ 2 [In2 Cl6 (bipy)] (1 ) and ∞ 2 [In2 Cl6 (bpe)] (2 ), the indium‐centered octahedra are linked by the bidentate linker only, but also a honeycomb‐like, zigzag‐shaped (6, 3)‐net with a hcb topology is formed. The CPs were investigated by SCXRD, PXRD, IR‐spectroscopy, and with DTA/TG regarding their thermal properties. Abstract :